The impact of glucagon-like peptide-1 (GLP-1) agonists in the treatment of eating disorders: a systematic review and meta-analysis - Hanieh Radkhah; Shiva Rahimipour Anaraki; Peyvand Parhizkar Roudsari; Razman Arabzadeh Bahri; Diar Zooravar; Sara Asgarian; Reza Hosseini Dolama; Ali Alirezaei; Razieh Khalooeifard (Eating and Weight Disorders)
Abstract Purpose Glucagon-like peptide-1 (GLP-1) receptor agonists have shown potential in managing eating disorders (EDs). Recent studies highlight their effects on pathophysiological pathways, indicating their therapeutic promise, particularly for binge eating disorder (BED). This systematic review evaluates the therapeutic effects of GLP-1 agonists on BED, focusing on weight management and eating behaviors. Methods A systematic search of PubMed, Scopus, Web of Science, and the Cochrane Library, along with manual searches, identified studies assessing GLP-1 agonists in BED patients up to November 8, 2024. Observational studies and clinical trials meeting inclusion criteria were analyzed. Results Five studies (182 participants) were included. Patients receiving GLP-1 agonists experienced greater weight loss (− 3.81 kg; 95% CI − 5.14 to − 2.49; p < 0.01, I 2: 59.88%) compared to controls. GLP-1 agonists significantly reduced BMI (− 1.48 kg/m2) and waist circumference (− 3.14 cm). Binge Eating Scale (BES) scores improved significantly (− 8.14 points; 95% CI − 13.13 to − 3.15; p < 0.01), though heterogeneity was noted. Conclusions This review underscores the potential role of GLP-1 agonists in BED management. However, given the limited data, especially concerning EDs other than BED and the long-term effects of these medications, further comprehensive clinical trials are recommended to evaluate the impact of various GLP-1 agonists on different EDs across diverse demographic groups. Level of evidence Level I, randomized controlled trials.